Xadrez e análise combinatória: a matemática do jogo - NEVES, Flávio de Lima das (2024)
The following research aims to illustrate the game of chess and Combinatorial Analysis, and to show how chess can be positively influenced in the lives of students, in the cognitive development of students, collaborating in the reduction of the damage caused to the learning of mathematics teaching, caused by the pandemic period, and thus substantiate the correlation between the game and Mathematics. The research was carried out in the higher elementary school, with the students of the 6th grade, of the Municipal School of Elementary Education Profª. Maria Madalena Ribeiro da Luz, in the interior of Curuçá, in the northeast region of Pará. For the methodological procedure, a qualitative approach was used, which was done through classroom observations. The students were the protagonists of this investigative study, where they were exceptional for the development of the research. The elaboration and realization of the project was thought out and minimally adapted to them, from the approach of the Game to the Combinatorial Analysis. The results are the adaptation of the students during the project, the restlessness and curiosity to learn, and the desire to teach what has been learned. This conclusion was made through conversation, perception, and questionnaire. Based on this result, the game is made as a model for the elaboration of more dynamic mathematics classes, without losing focus and with the active participation of students.